2005
DOI: 10.1021/es0487168
|View full text |Cite
|
Sign up to set email alerts
|

Pu(V)O2+ Adsorption and Reduction by Synthetic Hematite and Goethite

Abstract: Changes in aqueous- and solid-phase plutonium oxidation state were monitored over time in hematite (alpha-Fe2O3) and goethite (alpha-FeOOH) suspensions containing 239Pu(V)-amended 0.01 M NaCl. Solid-phase oxidation state distribution was quantified by leaching plutonium into the aqueous phase and applying an ultrafiltration/solvent extraction technique. The technique was verified using oxidation state analogues of plutonium and sediment-free controls of known Pu oxidation state. Batch kinetic experiments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
171
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(201 citation statements)
references
References 34 publications
27
171
3
Order By: Relevance
“…This is consistent with the observation of Pu(V) as the stable aqueous oxidation state in slightly acidic to neutral solutions including ocean and lake water and suspensions from Pu(IV) solubility experiments. Additionally, in all Pu sorption experiments where the oxidation state of the aqueous Pu fraction in a solid suspension was measured, Pu(V) was found to be the dominant oxidation state (Banik et al, 2007;Keeney-Kennicutt and Morse, 1985;Penrose et al, 1987;Powell et al, 2006;Powell et al, 2005;Powell et al, 2008;Sanchez et al, 1985). This was found to be the case for this work as well.…”
Section: Pu(iv) and Pu(v) Sorption To Gibbsitesupporting
confidence: 68%
See 2 more Smart Citations
“…This is consistent with the observation of Pu(V) as the stable aqueous oxidation state in slightly acidic to neutral solutions including ocean and lake water and suspensions from Pu(IV) solubility experiments. Additionally, in all Pu sorption experiments where the oxidation state of the aqueous Pu fraction in a solid suspension was measured, Pu(V) was found to be the dominant oxidation state (Banik et al, 2007;Keeney-Kennicutt and Morse, 1985;Penrose et al, 1987;Powell et al, 2006;Powell et al, 2005;Powell et al, 2008;Sanchez et al, 1985). This was found to be the case for this work as well.…”
Section: Pu(iv) and Pu(v) Sorption To Gibbsitesupporting
confidence: 68%
“…Surface mediated reduction of Pu(V) to Pu(IV) as discussed above is affected by pH. Powell et al (2005) found a -0.2 and -0.4 order dependence on the hydrogen ion concentration for the rate of Pu(V) reduction on goethite and hematite, respectively. Therefore, reduction of Pu(V) was expected to be more favored with increasing pH.…”
Section: Pu(iv) and Pu(v) Sorption To Gibbsitementioning
confidence: 73%
See 1 more Smart Citation
“…They found that the sorption rate was strongly pH-dependent for hematite, but only weakly pH-dependent for goethite. For both minerals, they found that, at pH values greater than pH 4.5, Pu(V) reduced to Pu(IV) on the surface of the goethite, with nearly complete adsorption and conversion within days or weeks, depending on the pH (Powell et al 2005 [DIRS 174726], Figures 2 and 3). For hematite, sorption of Pu(V) onto the surface was the rate-limiting step in the transformation; for goethite, reduction was the rate-limiting step.…”
Section: Sorption Dependence On Solution Compositionmentioning
confidence: 99%
“…Among the most ubiquitous inorganic colloids are aluminosilicate clays that are commonly observed as mobile colloids due to their inherently small particle size and prevalence as alteration minerals from original host rock material (Kersting et al, 1999). Clays are known to sorb Pu Keeney-Kennicutt and Morse, 1985;Kozai et al, 1996;Kozai et al, 1993;Lujaniene et al, 2007;Powell et al, 2004Powell et al, , 2005Powell et al, 2008;Sabodina et al, 2006;Sanchez et al, 1985;Turner et al, 1998). In addition, the proposed use of bentonite within some engineered barrier systems scenarios for high-level nuclear waste repositories provides additional importance to understanding Pu interaction with smectite aluminosilicate clays (Sabodina et al, 2006).…”
Section: Introductionmentioning
confidence: 99%